2006
DOI: 10.1038/sj.leu.2404141
|View full text |Cite
|
Sign up to set email alerts
|

hTERT, the catalytic component of telomerase, is downregulated in the haematopoietic stem cells of patients with chronic myeloid leukaemia

Abstract: Telomere shortening is associated with disease progression in chronic myeloid leukaemia (CML). To investigate the biology and regulation of telomerase in CML, we evaluated expression of the telomerase components, its regulators and several telomeric-associated proteins. Quantitative real-time-polymerase chain reaction (PCR) was used to compare gene expression in the CD34 þ /leukaemic blast cells of 22 CML patient samples to the CD34 þ cell population of healthy individuals. hTERT, the catalytic component of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 66 publications
0
36
1
1
Order By: Relevance
“…Interestingly TERC was found to be decreased in this study. In contrast Campbell et al (2006) demonstrated that the expression of TERT was decreased in CD34 + cells in CML patients in comparison to healthy individuals and that this decrease was present through all stages of the disease. It was felt that a possible explanation for these contradictory findings was related to the earlier methods used for measuring TA in unfractionated bone marrow samples, that did not allow for the increased percentage of blasts present in the marrow of BP patients in comparison to CP patients.…”
Section: Chronic Myeloid Leukaemiamentioning
confidence: 71%
See 1 more Smart Citation
“…Interestingly TERC was found to be decreased in this study. In contrast Campbell et al (2006) demonstrated that the expression of TERT was decreased in CD34 + cells in CML patients in comparison to healthy individuals and that this decrease was present through all stages of the disease. It was felt that a possible explanation for these contradictory findings was related to the earlier methods used for measuring TA in unfractionated bone marrow samples, that did not allow for the increased percentage of blasts present in the marrow of BP patients in comparison to CP patients.…”
Section: Chronic Myeloid Leukaemiamentioning
confidence: 71%
“…Campbell et al also demonstrated that MYC (a positive regulator of TERT) expression was highest in CP patients and decreased during disease progression to below the level of controls for patients in BP. This raised the possibility that decreased TERT expression is secondary to this fall in MYC (Wu et al, 1999;Campbell et al, 2006). These data show that CML cells have shortened telomeres (Table II).…”
Section: Chronic Myeloid Leukaemiamentioning
confidence: 77%
“…27,28 We have previously shown that TNKS (tankyrase), a TRF1-interacting factor that has an important role in the control of telomere dynamics, is upregulated in CP and accelerated phase CML. 10 The UPD at 8q11 was found in two CML patients. The most frequent UPD on chromosome 8 at 8q23, occurring in five patients, contained no known genes.…”
Section: Discussionmentioning
confidence: 99%
“…8 We have shown that telomere shortening and diminishing levels of hTERT are associated with disease evolution in CML. 9,10 Mutation of the tumor suppressor gene p53 is detected in B25-30% of CML-myeloid BC, 11 whereas B50% of the patients with lymphoid BC present a homozygous deletion of the INK4A/ARF gene. 12 Most recently, it has been shown that the loss of the IKAROS (IKZF1) gene is an important event in the development of lymphoid BC in CML and IKAROS is deleted in B80% of such patients.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to decreased levels of β-catenin and increased levels of phosphorylated β-catenin causing inhibition of the Wnt/β-catenin-driven proliferation of cancer cells. 9 Tankyrases are overexpressed in several human cancers, including breast cancer, 10 colon cancer, 11 chronic myeloid leukemia, 12 brain tumors, 13 and gastric 14 and bladder cancers. 15 There is 85% sequence homology between TNKS-1 and TNKS-2 within the ankyrin repeat, sterile alpha motif, and the NAD + -binding catalytic domains; the catalytic domains are 86% identical.…”
mentioning
confidence: 99%